2010
DOI: 10.1016/j.jep.2010.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Khat chewing, cardiovascular diseases and other internal medical problems: The current situation and directions for future research

Abstract: The leaves of khat (Catha edulis Forsk.) are chewed as a social habit for the central stimulant action of their cathinone content. This review summarizes the prevalence of the habit worldwide, the actions, uses, constituents and adverse health effects of khat chewing. There is growing concern about the health hazards of chronic khat chewing and this review concentrates on the adverse effects on health in the peripheral systems of the body, including the cardiovascular system and gastrointestinal tract. Compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
156
1
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(172 citation statements)
references
References 64 publications
11
156
1
4
Order By: Relevance
“…Al Motarreb et coll. [9] rapportent des doses plus élevées en cathinone, entre 78 et 343 mg pour 10 grammes de feuilles fraîches.…”
Section: Compositionunclassified
See 3 more Smart Citations
“…Al Motarreb et coll. [9] rapportent des doses plus élevées en cathinone, entre 78 et 343 mg pour 10 grammes de feuilles fraîches.…”
Section: Compositionunclassified
“…Les propriétés physiologiques et effets de la consommation du khat ont fait l'objet de plusieurs publications [8,9,[26][27][28][29]. On décrit une augmentation de la pression artérielle, une tachycardie, une insomnie, une anorexie, une constipation, une irritabilité, des migraines, une altération des performances sexuelles chez l'homme [12,15].…”
Section: Principaux Effets Cliniquesunclassified
See 2 more Smart Citations
“…Along with cathinone, other less potent stimulant substances are also present in khat leaves, namely norephedrine and norpseudoephedrine (cathinone) [5]. Taking into account the structural and pharmacological properties of amphetamine and cathinone, it can be concluded that they should act similarly by inducing dopamine releases from central dopaminergic nerve terminals, thus increasing the activity of dopaminergic pathways [6,7].…”
Section: Introductionmentioning
confidence: 99%